PENGARUH DIVERSITAS GENDER DEWAN KOMISARIS TERHADAP PENGHINDARAN PAJAK DENGAN SUSTAINABILITY PERFORMANCE SEBAGAI VARIABEL MEDIASI (Studi Empiris pada Perusahaan Non Keuangan yang Terdaftar di Bursa Efek Indonesia pada Tahun 2017-2019) - Bana, Elan Levita; Ghozali, Imam (Diponegoro Journal of Accounting, 2021)
This study aims to examine the direct association between board commissioner gender diversity with tax avoidance and the mediation effect of sustainability performance on this association. 65 samples selected of non financial sector companies listed on Indonesia Stock Exchange from the period 2017-2019. Multiple regression used to analyze the direct relationship between board commissioner gender diversity and tax avoidance. Path analysis approach was employed to analyze the indirect relationship between board commissioner gender diversity and tax avoidance through sustainability performance as mediating variable. The results show that board commissioner gender diversity has significant and positive effect on tax avoidance. This implies that gender diversity in board commissioner increases the level of tax avoidance. Board commissioner gender diversity has no significant influence on sustainability performance. Path analysis result did not find support for mediating role of sustainability performance on the relationship between board commissioner gender diversity and tax avoidance.